Les concentrations hivernales : une pratique touristique originale des motocyclistes européens à la recherche du froid et de la neige - Jean Scol (Confins)
Rally is a form of tourism highly developed in the motorcycling's world.. Among the almost 3,500 rallies organized each year in Europe, around ten percent are in winter. These so-called winter rallies are characterized by specific criteria. Their success and reputation depend largely on weather conditions paradoxically poorly adapted to the motorbike driving! They are therefore preferably organiezd in areas that offer roughest wintry conditions: (very) far to the north or to the east of the continent or very high altitudes. Locations at the origin of a real hierarchy between winter rallies themselves but also between motorcyclists who participate.